2010
DOI: 10.1111/j.1745-4557.2010.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrolyzed Oxidizing Water and Chlorinated Water Treatments on Strawberry and Broccoli Quality

Abstract: Strawberries and broccoli were treated for 5 min with 4C tap water, chlorinated water or electrolyzed oxidizing water (55 and 100 mg/L chlorine, respectively) with or without ultrasonication. Several quality parameters (weight loss, shear force, color, pH, titratable acidity, soluble solids and decay) were evaluated to estimate the effect of treatments on consumer acceptability during storage at 4C. Strawberries were examined on the initial day of experiments and at 3, 6, 9 and 13 days of storage, and broccoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…Untreated samples and samples treated with 25 mg/L ClO 2 , had the higher weight loss than other treated fruit during storage. It is possible to speculate that high concentration of ClO 2 oxidized the cell wall polymers and led to high water loss (Hung et al, 2010). Concentrations of 16 mg/L and 20 mg/L reduced the weight loss significantly at the end of the storage.…”
Section: Weight Lossmentioning
confidence: 99%
“…Untreated samples and samples treated with 25 mg/L ClO 2 , had the higher weight loss than other treated fruit during storage. It is possible to speculate that high concentration of ClO 2 oxidized the cell wall polymers and led to high water loss (Hung et al, 2010). Concentrations of 16 mg/L and 20 mg/L reduced the weight loss significantly at the end of the storage.…”
Section: Weight Lossmentioning
confidence: 99%
“…Bacterial counts on strawberry increased slightly to 2.5 log cfu/g after cold storage for 3 to 6 days; however, fungal counts did not increase after cold storage for 6 days. From a microbiological standpoint, our results for the bactericidal effects of SAHW on strawberry may contribute to the quality studies by Hung et al (2010); they reported that treatment of strawberries with EW (55 mg/L available chlorine, 5 min) resulted in no significant differences in color, shear force, weight loss, decay or chemical properties as compared with tap water. They also found that calcium hypochlorite treatment (100 mg/L available chlorine, 5 min) had greater negative effects on quality characteristics of strawberries than EW in terms of weight loss, shear force and decay.…”
Section: Discussionmentioning
confidence: 68%
“…This has motivated researchers to develop alternative pre-treatment strategies (Fenik et al, 2011). This include thermal or non-thermal treatments such as, hot water and electrolyzed water, which have emerged as a safe and effective techniques (Ferri et al, 2016;Hung et al, 2010;Usall et al, 2016).…”
Section: Introductionmentioning
confidence: 99%